An ultrasensitive aptasensor for chlorpyrifos based on ordered mesoporous carbon/ferrocene hybrid multiwalled carbon nanotubes. Issue 63 (17th June 2016) - Jiao, Yancui; Jia, Huiying; Guo, Yemin; Zhang, Haiyun; Wang, Zhiqiang; Sun, Xia; Zhao, Jing
Abstract : In this study, we designed a novel and ultrasensitive aptamer sensor for the quantitative detection of chlorpyrifos. Abstract : In this study, we designed a novel and ultrasensitive aptamer sensor for the quantitative detection of chlorpyrifos. To improve the sensitivity of the aptasensor, mesoporous carbon (OMC) functionalized by chitosan (OMC-CS) and ferrocene hybrid chitosan (CS) dispersed multiwalled carbon nanotubes (Fc@MWCNTs-CS) were modified on the electrode surface. OMC-CS has a high specific surface area, high porosity and ideal dispersibility which was used to efficiently capture larger amounts of material. Fc@MWCNTs-CS can efficiently capture more aptamer and increase electron transfer between the work electrode surface and potassium ferricyanide due to the good biocompatibility and electrical conductivity. The fabrication of the aptasensor was characterized using cyclic voltammetry, scanning electron microscopy and energy dispersive spectrometry. Under optimal conditions the designed aptasensor exhibited a wide linear range from 1 to 10 5 ng mL −1 with a low detection limit of 0.33 ng mL −1 (S/N = 3) for chlorpyrifos. The proposed chlorpyrifos aptasensor exhibited high selectivity, reproducibility and stability performance, which may open a new door for the ultrasensitive detection of chlorpyrifos residues in vegetables and fruits.